High-strength rare earth aluminum alloy material, preparation method and application

By optimizing alloy elements and preparation methods, high-performance aluminum alloy materials were developed, which solved the problem of insufficient strength and corrosion resistance of existing aluminum alloy fasteners in high temperature and vibration environments, and achieved high strength, plasticity and corrosion resistance and reduce production costs.

CN119307790AInactive Publication Date: 2025-01-14GUANGXI ZHENGLU MASCH TECH CO LTD

Patent Information

Application Number
CN202411462523.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the high temperature and vibration strength working environment, existing aluminum alloy fasteners have insufficient strength and corrosion resistance, making it difficult to meet the high-strength, high plasticity and high performance demands for high-speed development.

Method used

By reasonably optimizing alloy elements, adding rare earth elements lanthanum, samarium, ytterbium, etc., we develop high-performance aluminum alloy materials, and adopt specific preparation methods including smelting, mechanical stirring, refining, casting, extrusion and aging treatment to form high room temperature and aluminum alloy materials with high temperature mechanical properties.

Benefits of technology

It achieves the high strength, plasticity and corrosion resistance of aluminum alloy materials at room temperature and high temperature, meets the demand for high-performance fasteners and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a high-strength rare earth aluminum alloy material, a preparation method and application. The aluminum alloy material comprises, by weight, 0.2%-1.2% of Si, 0.2%-1.5% of Mg, 0.1%-0.2% of Cu, 0.1%-1.0% of Zn, 0.06%-1.0% of Mn, 0.06%-0.6% of Cr, 0.0.08%-0.3% of V, 0.03%-0.3% of Ag, 0.06%-0.4% of Ti, 0.01%-0.35% of Zr, 0.01%-0.35% of Hf, smaller than or equal to 0.20% of Fe, 0.03%-0.6% of La, 0.03%-0.4% of Yb, 0.03%-0.8% of Sm, smaller than or equal to 0.04% of other inevitable single impurity elements, smaller than or equal to 0.15% of the total amount of the impurity elements and the balance aluminum. In order to solve the problems of low room temperature strength, insufficient plasticity, poor thermal stability and the like of the existing 6000 series aluminum alloy, alloy elements are reasonably optimized, a proper amount of rare earth elements lanthanum, samarium and ytterbium are added, and a high-performance aluminum alloy material is developed and used for bolt manufacturing, so that the bolt has high room temperature strength, plasticity and thermal stability, and the service life of the bolt is prolonged. And the requirements of various fields for high-performance aluminum alloy bolts are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloy material processing, and in particular to a high-strength rare earth aluminum alloy material, a preparation method and application thereof. Background Art

[0002] With the development of society and the progress of industry, aluminum alloy materials have been increasingly used in the field of metal materials to improve the service life of equipment and facilities and the requirements of lightweight, such as aluminum alloy overpasses, aluminum alloy truss structures, aluminum alloy curtain walls, automobile bodies, engines, gearboxes, wheels, aluminum alloy pipes, etc. The above-mentioned components should be connected with related components of aluminum alloy fasteners, which can achieve lightweight, high strength, high plasticity, high performance and improved corrosion resistance of fasteners. At present, most of the aluminum alloy fasteners commonly used in the domestic market are produced by 6000 series aluminum alloy materials, and the main grades are 6061, 6082, etc. However, these aluminum alloy materials have low strength, tensile strength is lower than 330MPa, and elongation after fracture is lower than 14%, which is difficult to meet the high-speed development of the manufacturing industry for high-strength, high-plasticity, high-performance, and high-reliability fasteners. In addition, for aluminum alloy fasteners used in high temperature and high vibration intensity working environment, it is required to maintain high strength and corrosion resistance for a long time under high temperature conditions. At present, 6061 and 6082 aluminum alloys are difficult to meet the performance under these conditions. Therefore, it is urgent to develop an aluminum alloy material and fastener that not only has high strength, plasticity, and corrosion resistance at room temperature and high temperature environments, but also has controllable costs. To this end, in view of the low room temperature strength, insufficient plasticity, and poor thermal stability of 6000 series aluminum alloys, a high-performance aluminum alloy material is developed by rationally optimizing alloy elements and used in the manufacturing and processing of aluminum alloy fasteners to meet the needs of various fields for high-performance aluminum alloy fasteners, which has broad application prospects. Summary of the invention

[0003] The purpose of the present invention is to provide a high-strength rare earth aluminum alloy material, preparation method and application. The present invention aims at the problems of low room temperature strength, insufficient plasticity, poor thermal stability and the like of the current 6000 series aluminum alloy. By rationally optimizing the alloy elements and adding appropriate amounts of rare earth elements such as lanthanum, samarium and ytterbium, the present invention develops high-performance aluminum alloy materials and uses them in bolt manufacturing, so that the bolts have high room temperature strength, plasticity and thermal stability, so as to meet the needs of various fields for high-performance aluminum alloy bolts. In order to achieve the above purpose, the present invention adopts the following technical effects:

[0004] According to one aspect of the present invention, a high-strength rare earth aluminum alloy material is provided, which includes the following components in parts by weight: Si: 0.2-1.2%, Mg: 0.2-1.5%, Cu: 0.1-0.2%, Zn: 0.1-1.0%, Mn: 0.06-1.0%, Cr: 0.06-0.6%, V: 0.08-0.3%, Ag: 0.03-0.3%, Ti: 0.06-0.4%, Zr: 0.01-0.35%, Hf: 0.01-0.35%, Fe≤0.30%, La: 0.03-0.4%, Yb: 0.03-0.4%, Sm: 0.03-0.5%, other unavoidable single impurity elements≤0.04%, the total amount of impurity elements≤0.15%, and the balance is Al.

[0005] The above scheme is further preferred, that the aluminum alloy material includes the following components in parts by weight: Si: 0.6-1.0%, Mg: 0.6-1.4%, Cu: 0.1-0.2%, Zn: 0.4-0.8%, Mn: 0.3-0.6%, Cr: 0.08-0.3%, V: 0.1-0.25%, Ag: 0.05-0.15%, Ti: 0.06-0.30%, Zr: 0.08-0.20%, Hf: 0.05-0.18%, Fe≤0.20%, La: 0.08-0.3%, Yb: 0.05-0.20%, Sm: 0.05-0.30%, other unavoidable single impurity elements ≤0.03%, the total amount of impurity elements ≤0.15%, and the balance is Al.

[0006] The above scheme is further preferred, that the aluminum alloy material includes the following components in weight parts: Si: 0.63%, Mg: 1.29%, Cu: 0.13%, Zn: 0.58%, Mn: 0.43%, Cr: 0.26%, V: 0.21%, Ag: 0.11%, Ti: 0.16%, Zr: 0.10%, Hf: 0.18%, Fe: 0.19%, La: 0.33%, Yb: 0.21%, Sm: 0.15%, other unavoidable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, and the balance is Al.

[0007] According to another aspect of the present invention, the present invention provides a method for preparing a high-strength rare earth aluminum alloy material, the preparation method comprising the following steps:

[0008] Step (1), calculating and weighing the aluminum alloy raw material according to the mass percentage of the chemical composition of the alloy;

[0009] Step (2), firstly placing the prepared Al material in a melting furnace for smelting and melting, then adding Si, Cu, Zn, Mn, Cr, and V materials for melting, and then charging Ti, Zr, Hf, Fe, La, Yb, Sm, and Ag into the smelting furnace for heating and melting, and when the smelting temperature is reached, the smelting is carried out by keeping the temperature high, and mechanically stirring the melt during the holding period to obtain melt I;

[0010] Step (3), after cooling the melt I, Mg is added to the melt I for smelting, and melt II is obtained after the added charge is completely melted and fully stirred;

[0011] Step (4), performing a pre-furnace component test on melt II and adjusting the chemical composition according to the test results. If the composition is qualified, argon gas is introduced into melt II for refining and slag removal to obtain melt III; if the composition is unqualified, adjusting the alloy composition according to the test results until it is qualified, and performing refining and slag removal to obtain a final qualified melt III;

[0012] Step (5), discharging the melt III from the smelting furnace, and then entering a semi-continuous casting machine for casting after double-stage filtration to obtain a round rod-shaped ingot, the diameter of which is determined according to actual needs;

[0013] Step (6), placing the round rod-shaped ingot into a heating furnace, heating it and keeping it warm for a certain period of time for homogenization treatment, then taking the round rod-shaped ingot out of the heating furnace and cutting it into a certain length, and the remaining round rod-shaped ingot is again placed in the heating furnace for insulation, and the cut round rod-shaped ingot is placed in an extruder to be extruded into a rod of a desired diameter, and after the extruded rod is extruded from the extruder, it enters a water tank for machine quenching to cool it to room temperature, and then the rod is straightened and cut into a desired length;

[0014] Step (7), placing the extruded rod into an aging furnace for aging treatment, and after the heat preservation is completed, taking it out of the furnace and cooling it to room temperature to obtain a high-performance aluminum alloy material containing rare earth for subsequent processing.

[0015] The preparation method comprises the following steps: in step (2), the prepared Al material is placed in a melting furnace at a melting temperature of 550 to 780°C; when the melting temperature reaches 720 to 820°C, the melting is carried out by keeping the temperature constant; in step (3), Mg is added to the melt I and the melting temperature is 680 to 780°C.

[0016] The preparation method comprises the following steps: in step (4), the temperature of introducing argon gas into melt II for refining is 700-760°C, the refining time is 30-60 minutes, and the argon gas is 99.99% high-purity argon gas.

[0017] The preparation method comprises the following steps: in step (5), the casting temperature when entering the semi-continuous casting machine for casting is 680-720°C, and the crystallizer descending speed is 80-160 mm / min.

[0018] The preparation method comprises the following steps: in step (6), the homogenization treatment temperature is 500-575° C., the homogenization treatment time is ≥4 hours, and the extrusion speed is 6-16 m / min; in step (7), the extruded rod is placed in an aging furnace for aging treatment at an aging temperature of 120-220° C. and a holding time of 3-12 hours.

[0019] The preparation method comprises the following steps: the yield strength of the aluminum alloy material is 320-350 MPa, the tensile strength is 386-410 MPa, and the elongation is 18%-27%.

[0020] According to another aspect of the present invention, a high-strength rare earth aluminum alloy material of the present invention is used in aluminum alloy fasteners, and the aluminum alloy fasteners include but are not limited to bolts, clamps, nuts, screws, pins or washers. The preparation method of the aluminum alloy fasteners includes the following steps: firstly shearing the prepared high-strength rare earth aluminum alloy material into bars of the required length, then cold heading the bars into the required aluminum alloy fasteners, and then degreasing, pickling, alkali washing and anodizing to obtain the finished aluminum alloy fasteners. In the present invention, the high-strength rare earth aluminum alloy material of the present invention is used to process bolts, which includes the following steps: firstly shearing the prepared high-performance aluminum alloy bar containing rare earth into bars of the required length, then cold heading the bolt head, and then thread rolling the bolt to obtain the required thread to obtain the aluminum alloy bolt semi-finished product; finally, degreasing, pickling, alkali washing and anodizing the bolt semi-finished product to obtain the bolt finished product.

[0021] The reaction mechanism of the high-strength rare earth aluminum alloy material of the present invention is as follows:

[0022] First, the rare earth elements lanthanum (La), samarium (Sm), and ytterbium (Yb) all have a eutectic reaction at the aluminum-rich end of the Al-La, Al-Sm, and Al-Yb binary phase diagrams to generate Al 11 La3、Al 11 When the rare earth elements La, Sm, and Yb reach a certain content in the aluminum alloy, the rare earth elements will first crystallize and precipitate Al3Yb during the solidification process of the aluminum alloy melt. 11 La3、Al 11Sm3, Al3Yb intermediate phase, and Al3(Yb, Sm, La) intermediate phase formed by mutual doping of rare earth elements, these substances have L12 structure, which can play the role of heterogeneous nucleation core of α-Al grains during solidification, reduce the energy barrier of α-Al grain nucleation, and increase its nucleation rate, which is manifested as the effect of refining cast grains of aluminum alloy on a macro scale. The above intermediate phases also have a high melting point, and the diffusion coefficient of rare earth elements in aluminum alloys is low. The intermediate phases formed have high thermal stability, can maintain a low scale for a long time under high temperature environment, and have a low coarsening rate, which improves the high temperature strength and thermal stability of aluminum alloy materials. In addition, the above intermediate phases can hinder the migration of dislocations and grain boundaries and inhibit the recrystallization of aluminum alloys.

[0023] Secondly, Mn, Cr, and V elements can form α-Al(Mn,Cr,V,Fe)Si intermediate phase in 6000 series aluminum alloys. On the one hand, the morphology of the Fe-rich phase can be improved by doping the Fe-rich phase with Mn, Cr, and V elements; on the other hand, the α-Al(Mn,Cr,V,Fe)Si intermediate phase can have a certain hindering effect on the migration of dislocations and grain boundaries of aluminum alloys, and has a certain effect of inhibiting the recrystallization of aluminum alloys.

[0024] Thirdly, Ti, Zr, and Hf are in the same family and react with Al in alloys with lower content to form Al3Ti, Al3Zr, and Al3Hf intermediate phases with D019 structure, which play the role of heterogeneous nucleation core for the nucleation of α-Al grains, improve the nucleation rate of α-Al grains, and show the effect of refining the cast grains of aluminum alloy on a macro scale. In addition, Ti, Zr, and Hf elements can also interact with rare earth elements to generate inter-doped Al3 (Ti, Zr, Hf, La, Sm, Yb) intermediate phases with "core / shell" structure. These intermediate phases have L12 structure, and their grain refining effect is better than Al3Ti, Al3Zr, and Al3Hf intermediate phases. By improving the micro-alloying elements such as Ti, La, Zr, Sm, Hf and Yb, the microstructure of aluminum alloy is effectively improved, and the comprehensive performance is improved, so as to improve the strength of aluminum alloy and its fracture toughness, and solve the technical problems related to the existing high-strength aluminum alloy due to low strength and inability to meet the requirements of high load and light weight;

[0025] Finally, during the aging process of 6000 series aluminum alloys, Cu and Ag elements dope the β" (Mg5Si6) phase, enrich on the surface of the β" (Mg5Si6) phase, reduce the surface energy between the β" phase and α-Al grains, and thus improve the thermal stability of the β" phase.

[0026] In summary, the present invention adopts the above technical solution, and the present invention has the following technical effects:

[0027] (1) The present invention forms Al alloy during the solidification and heat treatment process of aluminum alloy through the interaction between rare earth elements La, Sm, Yb and Ti, Zr, Hf and other elements. 11 La3、Al 11 Intermediate phases such as Sm3, Al3Yb, Al3(Yb, Sm, La), Al3Ti, Al3Zr, Al3Hf, Al3(Ti, Zr, Hf, La, Sm, Yb). The existence of these intermediate phases is determined by the content of the above elements in the actual alloy composition, and not all of the above intermediate phases actually exist. The effects of the above intermediate phases, such as refining the cast grains of aluminum alloy, inhibiting recrystallization, and improving thermal stability, are utilized to achieve the purpose of improving the room temperature and high temperature mechanical properties, plasticity, and corrosion resistance of the alloy material and meet the requirements of lightweight aluminum alloy.

[0028] (2) The present invention utilizes the improvement of the Fe-rich phase morphology and the inhibition of recrystallization by Mn, Cr, and V elements to improve the room temperature mechanical properties of aluminum alloy materials.

[0029] (3) The present invention improves the thermal stability of the β" (Mg5Si6) phase on a microscopic scale by rationally adding Cu and Ag elements, thereby achieving the purpose of improving the high-temperature mechanical properties of the alloy material.

[0030] (4) The present invention prepares a high-performance 6000 series aluminum alloy material and its aluminum alloy fastener preparation method that is superior to the traditional extrusion process by reasonably optimizing the ratio of the main alloying elements Si and Mg, and reasonably adding various alloying elements, especially rare earth elements. The prepared aluminum alloy fasteners have high room temperature mechanical properties, plasticity, high temperature mechanical properties and corrosion resistance, and can meet the demand of the development of the manufacturing industry for new aluminum alloy materials and aluminum alloy fasteners. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, preferred embodiments are given below to further describe the present invention in detail. However, it should be noted that many details listed in the specification are only for the purpose of enabling the reader to have a thorough understanding of one or more aspects of the present invention, and these aspects of the present invention can be implemented even without these specific details.

[0032] Example 1

[0033] According to a high-strength rare earth aluminum alloy material of the present invention, the aluminum alloy material includes the following components in parts by weight: Si: 1.2%, Mg: 0.2%, Cu: 0.1%, Zn: 0.1%, Mn: 0.06%, Cr: 0.06%, V: 0.08%, Ag: 0.03%, Ti: 0.06%, Zr: 0.01%, Hf: 0.01%, Fe≤0.30%, La: 0.03%, Yb: 0.03%, Sm: 0.03%, other unavoidable single impurity elements≤0.04%, the total amount of impurity elements≤0.15%, and the balance is Al.

[0034] The embodiment of the present invention provides a method for preparing a high-strength rare earth aluminum alloy material, comprising the following steps:

[0035] Step (1), calculating and weighing the raw materials according to the mass percentage of the chemical composition of the alloy;

[0036] Step (2), firstly placing the prepared Al material in a melting furnace for smelting at 550°C, then adding Si, Cu, Zn, Mn, Cr, and V materials for melting, and then charging Ti, Zr, Hf, Fe, La, Yb, Sm, and Ag into the melting furnace for heating and melting, and when the melting temperature reaches 720°C, the melting is kept at the temperature for smelting, and the melt is mechanically stirred during the holding period to obtain melt I;

[0037] Step (3), when the temperature of melt I drops to 680°C, Mg is added to melt I for smelting, and the smelting temperature is raised to 700°C, and the added charge is completely melted and fully stirred to obtain melt II;

[0038] Step (4), performing a pre-furnace component test on melt II and adjusting the chemical composition according to the test results. If the composition is qualified, 99.99% high-purity argon gas is introduced into melt II for refining and slag removal, the refining temperature is 700° C., and the refining time is 60 min to obtain melt III; if the composition is unqualified, adjusting the alloy composition according to the test results until it is qualified, and refining and slag removal are performed to obtain a final qualified melt III gas;

[0039] Step (5), discharging the melt III from the smelting furnace, filtering it through a double stage, and then entering a semi-continuous casting machine for casting, the casting temperature is 680° C., the crystallizer descending speed is 160 mm / min, and a round rod-shaped ingot with a diameter of 178 mm is obtained;

[0040] Step (6), placing the round rod-shaped ingot into a heating furnace, heating it to 500° C. and keeping it warm for 8 hours for homogenization treatment, then taking the round rod-shaped ingot out of the heating furnace and cutting it into a 500 mm length, and the remaining round rod-shaped ingot is again placed in the heating furnace for insulation, and the cut round rod-shaped ingot is placed in an extruder and extruded into a rod with a diameter of 10 mm, and the extrusion speed is 16 m / min. After the extruded rod is extruded from the extruder, it enters a water tank for machine quenching to cool it to room temperature, and then the rod is straightened and cut into a length of 6 m;

[0041] Step (7), placing the extruded rod with a diameter of 10 mm and a length of 6 m into an aging furnace for aging treatment, the aging temperature of the aging treatment is 120° C., the insulation time is 12 hours, and after the insulation is completed, the rod is taken out of the furnace and cooled to room temperature to obtain a high-performance aluminum alloy material containing rare earth for subsequent processing.

[0042] The process of processing a high-strength rare earth aluminum alloy material prepared by the invention into a bolt is as follows: a high-performance aluminum alloy material containing rare earth with a diameter of 10 mm is sheared into bars of the required length, and then the bolt head is processed on a cold heading machine, and then the bolt head is cold headed, and the required thread is rolled to obtain a semi-finished aluminum alloy bolt; finally, the semi-finished bolt is degreased, pickled, alkali washed and anodized to obtain a M10 bolt finished product.

[0043] Example 2

[0044] According to a high-strength rare earth aluminum alloy material of the present invention, the aluminum alloy material includes the following components in parts by weight: Si: 0.2%, Mg: 1.5%, Cu: 0.2%, Zn: 1.0%, Mn: 1.0%, Cr: 0.6%, V: 0.3%, Ag: 0.3%, Ti: 0.4%, Zr: 0.35%, Hf: 0.35%, Fe≤0.10%, La: 0.4%, Yb: 0.4%, Sm: 0.5%, other unavoidable single impurity elements ≤0.01%, the total amount of impurity elements ≤0.08%, and the balance is Al.

[0045] A method for preparing a high-strength rare earth aluminum alloy material of the present invention comprises the following steps:

[0046] Step (1), calculating and weighing the raw materials according to the mass percentage of the chemical composition of the alloy;

[0047] Step (2), firstly placing the prepared Al material in a melting furnace for smelting at 780°C, then adding Si, Cu, Zn, Mn, Cr, and V materials for melting, and then charging Ti, Zr, Hf, Fe, La, Yb, Sm, and Ag into the melting furnace for heating and melting, and when the melting temperature reaches 820°C, the melting is kept at the temperature for smelting, and the melt is kept mechanically stirred during the holding period to obtain melt I;

[0048] Step (3), when the temperature of melt I drops to 680° C., Mg is added to melt I for smelting, and the smelting temperature is then increased to 780° C. The added charge is completely melted and fully stirred to obtain melt II;

[0049] Step (4), performing a pre-furnace component test on melt II and adjusting the chemical composition according to the test results. If the composition is qualified, 99.99% high-purity argon gas is introduced into melt II for refining and slag removal, the refining temperature is 760° C., and the refining time is 30 min to obtain melt III; if the composition is unqualified, adjusting the alloy composition according to the test results until it is qualified, and refining and slag removal are performed to obtain a final qualified melt III;

[0050] Step (5), discharging melt III from the smelting furnace, and then entering a semi-continuous casting machine for casting after double-stage filtration, with a casting temperature of 720° C. and a crystallizer descending speed of 80 mm / min, to obtain a round rod-shaped ingot with a diameter of 178 mm;

[0051] Step (6), placing the round rod-shaped ingot into a heating furnace, heating it to 500° C. and keeping it warm for 4 hours for homogenization treatment, then taking the round rod-shaped ingot out of the heating furnace and cutting it into a 500 mm length, and the remaining round rod-shaped ingot is again placed in the heating furnace for insulation, and the cut round rod-shaped ingot is placed in an extruder and extruded into a rod with a diameter of 10 mm, and the extrusion speed is 16 m / min. After the extruded rod is extruded from the extruder, it enters a water tank for machine quenching to cool it to room temperature, and then the rod is straightened and cut into a length of 6 m;

[0052] Step (7), placing the extruded rod with a diameter of 10 mm and a length of 6 m into an aging furnace for aging treatment, the aging temperature of the aging treatment is 220° C., the insulation time is 3 hours, and after the insulation is completed, the rod is taken out of the furnace and cooled to room temperature to obtain a high-performance aluminum alloy material containing rare earth for subsequent processing.

[0053] The process of processing a high-strength rare earth aluminum alloy material prepared by the invention into a bolt is as follows: a high-performance aluminum alloy material containing rare earth with a diameter of 10 mm is sheared into bars of the required length, and then the bolt head is processed on a cold heading machine, and then the bolt head is cold headed, and the required thread is rolled to obtain a semi-finished aluminum alloy bolt; finally, the semi-finished bolt is degreased, pickled, alkali washed and anodized to obtain a M10 bolt finished product.

[0054] Example 3

[0055] According to a high-strength rare earth aluminum alloy material of the present invention, the aluminum alloy material includes the following components in parts by weight: Si: 1.0%, Mg: 0.6%, Cu: 0.1%, Zn: 0.4%, Mn: 0.3%, Cr: 0.08%, V: 0.1%, Ag: 0.05%, Ti: 0.06%, Zr: 0.08%, Hf: 0.05%, Fe≤0.20%, La: 0.08%, Yb: 0.05%, Sm: 0.05%, other unavoidable single impurity elements ≤0.02%, the total amount of impurity elements ≤0.1%, and the balance is Al.

[0056] A method for preparing a high-strength rare earth aluminum alloy material of the present invention comprises the following steps:

[0057] Step (1), calculating and weighing the raw materials according to the mass percentage of the chemical composition of the alloy;

[0058] Step (2), firstly placing the prepared Al material in a melting furnace for smelting at 650°C, then adding Si, Cu, Zn, Mn, Cr, and V materials for melting, and then charging Ti, Zr, Hf, Fe, La, Yb, Sm, and Ag into the melting furnace for heating and melting, and when the melting temperature reaches 780°C, the melting is kept at the temperature for smelting, and the melt is kept mechanically stirred during the holding period to obtain melt I;

[0059] Al, Si, Cu, Zn, Mn, Cr, V, Ti, Zr, Hf, Fe, La, Yb, Sm and Ag are placed in a smelting furnace and heated to melt. When the smelting temperature reaches 840°C, the smelting is carried out by keeping the temperature high and mechanically stirring the melt during the holding period to obtain melt I.

[0060] Step (3), when the temperature of melt I drops to 720° C., Mg is added to melt I for smelting, and the smelting temperature is then raised to 720° C., and the added charge is completely melted and fully stirred to obtain melt II;

[0061] Step (4), performing a pre-furnace component test on melt II and adjusting the chemical composition according to the test results. If the composition is qualified, 99.99% high-purity argon gas is introduced into melt II for refining and slag removal, the refining temperature is 720° C., and the refining time is 40 min to obtain melt III; if the composition is unqualified, adjusting the alloy composition according to the test results until it is qualified, and refining and slag removal are performed to obtain a final qualified melt III;

[0062] Step (5), discharging the melt III from the smelting furnace, filtering it through a double stage, and then entering a semi-continuous casting machine for casting, the casting temperature is 690° C., the crystallizer descending speed is 100 mm / min, and a round rod-shaped ingot with a diameter of 178 mm is obtained;

[0063] Step (6), placing the round rod-shaped ingot into a heating furnace, heating it to 520° C. and keeping it warm for 6 hours for homogenization treatment, then taking the round rod-shaped ingot out of the heating furnace and cutting it into a 500 mm length, and the remaining round rod-shaped ingot is again placed in the heating furnace for insulation, and the cut round rod-shaped ingot is placed in an extruder and extruded into a rod with a diameter of 10 mm, and the extrusion speed is 12 m / min. After the extruded rod is extruded from the extruder, it enters a water tank for machine quenching to cool it to room temperature, and then the rod is straightened and cut into a length of 6 m;

[0064] Step (7), placing the extruded rod with a diameter of 10 mm and a length of 6 m into an aging furnace for aging treatment, the aging temperature of the aging treatment is 175° C., the insulation time is 13 hours, and after the insulation is completed, the rod is taken out of the furnace and cooled to room temperature to obtain a high-performance aluminum alloy material containing rare earth for subsequent processing.

[0065] The process of processing a high-strength rare earth aluminum alloy material prepared by the invention into a bolt is as follows: a high-performance aluminum alloy material containing rare earth with a diameter of 10 mm is sheared into bars of the required length, and then the bolt head is processed on a cold heading machine, and then the bolt head is cold headed, and the required thread is rolled to obtain a semi-finished aluminum alloy bolt; finally, the semi-finished bolt is degreased, pickled, alkali washed and anodized to obtain a M10 bolt finished product.

[0066] Example 4

[0067] According to a high-strength rare earth aluminum alloy material of the present invention, the aluminum alloy material includes the following components in parts by weight: Si: 1.0%, Mg: 1.4%, Cu: 0.2%, Zn: 0.8%, Mn: 0.6%, Cr: 0.3%, V: 0.25%, Ag: 0.15%, Ti: 0.30%, Zr: 0.20%, Hf: 0.18%, Fe≤0.20%, La: 0.3%, Yb: 0.20%, Sm: 0.30%, other unavoidable single impurity elements≤0.25%, the total amount of impurity elements≤0.10%, and the balance is Al.

[0068] A method for preparing a high-strength rare earth aluminum alloy material of the present invention comprises the following steps:

[0069] Step (1), calculating and weighing the raw materials according to the mass percentage of the chemical composition of the alloy;

[0070] Step (2), firstly placing the prepared Al material in a melting furnace at 620°C for smelting and melting, then adding Si, Cu, Zn, Mn, Cr, and V materials for melting, and then charging Ti, Zr, Hf, Fe, La, Yb, Sm, and Ag into the smelting furnace for heating and melting, and when the temperature reaches the smelting temperature of 800°C, the smelting is carried out by keeping the temperature high, and mechanically stirring the melt during the insulation period to obtain melt I;

[0071] Step (3), when the temperature of melt I drops to 650° C., Mg is added to melt I for smelting, and the smelting temperature is then increased to 740° C. The added charge is completely melted and fully stirred to obtain melt II;

[0072] Step (4), performing a pre-furnace component test on melt II and adjusting the chemical composition according to the test results. If the composition is qualified, 99.99% high-purity argon gas is introduced into melt II for refining and slag removal, the refining temperature is 740° C., and the refining time is 45 min to obtain melt III; if the composition is unqualified, adjusting the alloy composition according to the test results until it is qualified, and refining and slag removal are performed to obtain a final qualified melt III;

[0073] Step (5), discharging the melt III from the smelting furnace, and then entering a semi-continuous casting machine for casting after double-stage filtration, the casting temperature is 700° C., the crystallizer descending speed is 120 mm / min, and a round rod-shaped ingot with a diameter of 178 mm is obtained;

[0074] Step (6), placing the round rod-shaped ingot into a heating furnace, heating it to 540° C. and keeping it warm for 6 hours for homogenization treatment, then taking the round rod-shaped ingot out of the heating furnace and cutting it into a 500 mm length, and the remaining round rod-shaped ingot is again placed in the heating furnace for insulation, and the cut round rod-shaped ingot is placed in an extruder and extruded into a rod with a diameter of 10 mm, and the extrusion speed is 12 m / min. After the extruded rod is extruded from the extruder, it enters a water tank for machine quenching to cool it to room temperature, and then the rod is straightened and cut into a length of 6 m;

[0075] Step (7), placing the extruded rod with a diameter of 10 mm and a length of 6 m into an aging furnace for aging treatment, the aging temperature of the aging treatment is 195° C., the insulation time is 10 hours, and after the insulation is completed, the rod is taken out of the furnace and cooled to room temperature to obtain a high-performance aluminum alloy material containing rare earth for subsequent processing.

[0076] The process of processing a high-strength rare earth aluminum alloy material prepared by the invention into a bolt is as follows: a high-performance aluminum alloy material containing rare earth with a diameter of 10 mm is sheared into bars of the required length, and then the bolt head is processed on a cold heading machine, and then the bolt head is cold headed, and the required thread is rolled to obtain a semi-finished aluminum alloy bolt; finally, the semi-finished bolt is degreased, pickled, alkali washed and anodized to obtain a M10 bolt finished product.

[0077] Example 5

[0078] According to a high-strength rare earth aluminum alloy material of the present invention, the aluminum alloy material includes the following components in parts by weight: Si: 0.6%, Mg: 1.2%, Cu: 0.16%, Zn: 0.69%, Mn: 0.63%, Cr: 0.40%, V: 0.16%, Ag: 0.08%, Ti: 0.10%, Zr: 0.13%, Hf: 0.09%, Fe: 0.18%, La: 0.26%, Yb: 0.12%, Sm: 0.14%, other unavoidable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, and the balance is aluminum.

[0079] A method for preparing a high-strength rare earth aluminum alloy material of the present invention comprises the following steps:

[0080] Step (1), calculating and weighing the raw materials according to the mass percentage of the chemical composition of the alloy;

[0081] Step (2), firstly placing the prepared Al material in a melting furnace for smelting at 600°C, then adding Si, Cu, Zn, Mn, Cr, and V materials for melting, and then charging Ti, Zr, Hf, Fe, La, Yb, Sm, and Ag into the melting furnace for heating and melting, and when the melting temperature reaches 750°C, the melting is kept at the temperature for smelting, and the melt is mechanically stirred during the holding period to obtain melt I;

[0082] Step (3), when the temperature of melt I drops to 710° C., Mg is added to melt I for smelting, and the smelting temperature is then increased to 740° C. The added charge is completely melted and fully stirred to obtain melt II;

[0083] Step (4), performing a pre-furnace component test on melt II and adjusting the chemical composition according to the test results. If the composition is qualified, 99.99% high-purity argon gas is introduced into melt II for refining and slag removal, the refining temperature is 730° C., and the refining time is 50 min to obtain melt III; if the composition is unqualified, adjusting the alloy composition according to the test results until it is qualified, and refining and slag removal are performed to obtain a final qualified melt III;

[0084] Step (5), discharging melt III from the smelting furnace, and then entering a semi-continuous casting machine for casting after double-stage filtration, with a casting temperature of 705° C. and a crystallizer descending speed of 115 mm / min, to obtain a round rod-shaped ingot with a diameter of 178 mm;

[0085] Step (6), placing the round rod-shaped ingot into a heating furnace, heating it to 545° C. and keeping it warm for 6 hours for homogenization treatment, then taking the round rod-shaped ingot out of the heating furnace and cutting it into a 500 mm length, and the remaining round rod-shaped ingot is again placed in the heating furnace for insulation, and the cut round rod-shaped ingot is placed in an extruder and extruded into a rod with a diameter of 10 mm, and the extrusion speed is 8 m / min. After the extruded rod is extruded from the extruder, it enters a water tank for machine quenching to cool it to room temperature, and then the rod is straightened and cut into a length of 6 m;

[0086] Step (7), placing the extruded rod with a diameter of 10 mm and a length of 6 m into an aging furnace for aging treatment, the aging temperature of the aging treatment is 190° C., the insulation time is 4 hours, and after the insulation is completed, the rod is taken out of the furnace and cooled to room temperature to obtain a high-performance aluminum alloy material containing rare earth for subsequent processing.

[0087] The process of processing a high-strength rare earth aluminum alloy material prepared by the invention into a bolt is as follows: a high-performance aluminum alloy material containing rare earth with a diameter of 10 mm is sheared into bars of the required length, and then the bolt head is processed on a cold heading machine, and then the bolt head is cold headed, and the required thread is rolled to obtain a semi-finished aluminum alloy bolt; finally, the semi-finished bolt is degreased, pickled, alkali washed and anodized to obtain a M10 bolt finished product.

[0088] Example 6

[0089] According to a high-strength rare earth aluminum alloy material of the present invention, the aluminum alloy material includes the following components in parts by weight: Si: 0.76%, Mg: 1.18%, Cu: 0.11%, Zn: 0.46%, Mn: 0.58%, Cr: 0.39%, V: 0.19%, Ag: 0.06%, Ti: 0.09%, Zr: 0.11%, Hf: 0.09%, Fe: 0.16%, La: 0.17%, Yb: 0.13%, Sm: 0.18%, other unavoidable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, and the balance is aluminum.

[0090] The embodiment of the present invention provides a method for preparing a high-strength rare earth aluminum alloy material, the method comprising the following steps: step (1), calculating and weighing raw materials according to the mass percentage of the chemical composition of the alloy;

[0091] Step (2), firstly placing the prepared Al material in a melting furnace for smelting at 670°C, then adding Si, Cu, Zn, Mn, Cr, and V materials for melting, and then charging Ti, Zr, Hf, Fe, La, Yb, Sm, and Ag into the melting furnace for heating and melting, and when the melting temperature reaches 760°C, the melting is kept at the temperature for smelting, and the melt is mechanically stirred during the holding period to obtain melt I;

[0092] (3) When the temperature of melt I drops to 695°C, Mg is added to melt I for smelting, and the smelting temperature is then increased to 735°C. The added charge is completely melted and fully stirred to obtain melt II;

[0093] (4) Conducting a pre-furnace component test on melt II and adjusting the chemical composition according to the test results. If the composition is qualified, 99.99% high-purity argon gas is introduced into melt II for refining and slag removal. The refining temperature is 735°C and the refining time is 60 min to obtain melt III. If the composition is unqualified, the alloy composition is adjusted according to the test results until it is qualified, and refining and slag removal are performed to obtain the final qualified melt III.

[0094] (5) Melt III is discharged from the smelting furnace, and then enters a semi-continuous casting machine for casting after double-stage filtration. The casting temperature is 710° C. and the crystallizer descending speed is 115 mm / min, and a round rod-shaped ingot with a diameter of 178 mm is obtained;

[0095] (6) placing the round rod-shaped ingot in a heating furnace, heating it to 545° C. and keeping it warm for 6 hours for homogenization treatment, then taking the round rod-shaped ingot out of the heating furnace and cutting it into a length of 450 mm, and the remaining round rod-shaped ingot is again placed in the heating furnace for insulation, and the cut round rod-shaped ingot is placed in an extruder and extruded into a rod with a diameter of 20 mm, and the extrusion speed is 9 m / min. After the extruded rod is extruded from the extruder, it enters a water tank for machine quenching to cool it to room temperature, and then the rod is straightened and cut into a length of 6 m;

[0096] (7) The extruded rod with a diameter of 20 mm and a length of 6 m is placed in an aging furnace for aging treatment. The aging temperature of the aging treatment is 180° C. and the insulation time is 8 hours. After the insulation is completed, the rod is taken out of the furnace and cooled to room temperature to obtain a high-performance aluminum alloy material containing rare earth for subsequent processing.

[0097] The process of processing a high-strength rare earth aluminum alloy material prepared by the invention into a bolt is as follows: a high-performance aluminum alloy material containing rare earth with a diameter of 20 mm is sheared into bars of a required length, and then a bolt head is processed on a cold heading machine, and then the bolt head is cold headed, and the required thread is rolled to obtain a semi-finished aluminum alloy bolt; finally, the semi-finished bolt is degreased, pickled, alkali washed and anodized to obtain a finished M20 bolt.

[0098] Example 7

[0099] According to a high-strength rare earth aluminum alloy material of the present invention, the aluminum alloy material includes the following components in parts by weight: Si: 0.63%, Mg: 1.29%, Cu: 0.13%, Zn: 0.58%, Mn: 0.43%, Cr: 0.26%, V: 0.21%, Ag: 0.11%, Ti: 0.16%, Zr: 0.10%, Hf: 0.18%, Fe: 0.19%, La: 0.33%, Yb: 0.21%, Sm: 0.15%, other unavoidable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, and the balance is aluminum.

[0100] A method for preparing a high-strength rare earth aluminum alloy material of the present invention comprises the following steps:

[0101] Step (1), calculating and weighing the raw materials according to the mass percentage of the chemical composition of the alloy;

[0102] Step (2), firstly placing the prepared Al material in a melting furnace for smelting at 590°C, then adding Si, Cu, Zn, Mn, Cr, and V materials for melting, and then charging Ti, Zr, Hf, Fe, La, Yb, Sm, and Ag into the melting furnace for heating and melting, and when the melting temperature reaches 770°C, the melting is kept at the temperature for smelting, and the melt is kept mechanically stirred during the holding period to obtain melt I;

[0103] Step (3), when the temperature drops to 700°C, Mg is added to the melt I for smelting, and the smelting temperature is then increased to 730°C. The added charge is completely melted and fully stirred to obtain the melt II;

[0104] Step (4), performing a pre-furnace component test on melt II and adjusting the chemical composition according to the test results. If the composition is qualified, 99.99% high-purity argon gas is introduced into melt II for refining and slag removal, the refining temperature is 720° C., and the refining time is 50 min to obtain melt III; if the composition is unqualified, adjusting the alloy composition according to the test results until it is qualified, and refining and slag removal are performed to obtain a final qualified melt III;

[0105] Step (5), discharging the melt III from the smelting furnace, and then entering a semi-continuous casting machine for casting after double-stage filtration, the casting temperature is 700° C., the crystallizer descending speed is 145 mm / min, and a round rod-shaped ingot with a diameter of 178 mm is obtained;

[0106] Step (6), placing the round rod-shaped ingot into a heating furnace, heating it to 530° C. and keeping it warm for 6 hours for homogenization treatment, then taking the round rod-shaped ingot out of the heating furnace and cutting it into a 450 mm length, and the remaining round rod-shaped ingot is again placed in the heating furnace for insulation, and the cut round rod-shaped ingot is placed in an extruder and extruded into a rod with a diameter of 6 mm, and the extrusion speed is 10 m / min. After the extruded rod is extruded from the extruder, it enters a water tank for machine quenching to cool it to room temperature, and then the rod is straightened and cut into a length of 6 m;

[0107] Step (7), placing the extruded rod with a diameter of 6 mm and a length of 6 m into an aging furnace for aging treatment, the aging temperature of the aging treatment is 180° C., the insulation time is 8 hours, and after the insulation is completed, the rod is taken out of the furnace and cooled to room temperature to obtain a high-performance aluminum alloy material containing rare earth for subsequent processing.

[0108] The process of processing a high-strength rare earth aluminum alloy material prepared by the invention into a bolt is as follows: the high-performance aluminum alloy material containing rare earth with a diameter of 6 mm is sheared into a bar of the required length, and then the bolt head is processed on a cold heading machine, and then the bolt head is cold headed, and the required thread is rolled to obtain a semi-finished aluminum alloy bolt; finally, the semi-finished bolt is degreased, pickled, alkali washed and anodized to obtain a finished M20 bolt.

[0109] In the present invention, the high-strength rare earth aluminum alloy material prepared by the present invention can also be processed into aluminum alloy fasteners such as clamps, nuts, screws, pins or washers. The obtained aluminum alloy fasteners have lightweight, high room temperature mechanical properties, plasticity, high temperature mechanical properties and corrosion resistance, and can meet the needs of new aluminum alloy materials and their aluminum alloy fastener processing.

[0110] Comparative Example 1

[0111] Bolts produced with 6061 aluminum alloy are used for comparison. The mass percentage of 6061 alloy components is: Si: 0.62%, Mg: 1.05%, Cu: 0.21%, Mn: 0.11%, Cr: 0.13%, Fe: 0.28%, Ti: 0.10%, other unavoidable single impurity elements ≤ 0.05%, the total amount of impurity elements ≤ 0.15%, and the balance is aluminum. 6061 alloy is smelted, cast, extruded, and aged to make rods with a diameter of 10mm, and then sheared, cold headed, threaded, degreased, pickled, alkali washed, and anodized to make M10 bolts.

[0112] Comparative Example 2

[0113] Bolts produced with 6082 aluminum alloy are used for comparison. The mass percentage of 6082 alloy composition is: Si: 1.16%, Mg: 0.83%, Cu: 0.05%, Mn: 0.84%, Cr: 0.15%, Zn: 0.20%, Fe: 0.28%, Ti: 0.06%, other unavoidable single impurity elements ≤ 0.05%, the total amount of impurity elements ≤ 0.15%, and the balance is aluminum. 6082 alloy is smelted, cast, extruded, and aged to make rods with a diameter of 10mm, and then sheared, cold headed, threaded, degreased, pickled, alkali washed, and anodized to make M10 bolts.

[0114] Comparative Example 3

[0115] Bolts made of 304 stainless steel are used for comparison. The mass percentage of 304 stainless steel components is: C: 0.06%, Si: 0.75%, Mn: 1.68%, P: 0.02%, S: 0.02%, Ni: 8.53%, Cr: 18.4%, and the remaining impurities are ≤ 0.03%, and the balance is iron. 304 stainless steel is made into 10mm diameter bars through smelting, continuous casting, hot rolling, and solution treatment, and then sheared, cold headed, thread rolled, degreased, pickled, and passivated to make M10 bolts.

[0116] Performance Testing

[0117] The bolts prepared in the above Examples 1-7 and Comparative Examples 1-3 were tested on the aluminum alloy materials and the bolts prepared in accordance with the relevant requirements of GB / T228-2010 and GB / T3098.1-2010 as follows:

[0118] 1. Room temperature mechanical properties test

[0119] The room temperature mechanical properties of the bolts were measured using a tensile machine, and the results are shown in Table 1.

[0120] Table 1 Mechanical properties test results of bolts

[0121] Alloy Material state Yield strength / MPa Tensile strength(MPa) Elongation(%) Fatigue strength(MPa) Example 1 T6 376 456 23.2 158 Example 2 T6 402 474 24.2 162 Example 3 T6 390 462 23.5 159 Example 4 T6 414 496 22.6 157.2 Example 5 T6 384 463 24.1 160.1 Example 6 T6 396 479 23.7 159.8 Example 7 T6 407 491 22.8 156.6 6061 Aluminum Alloy T6 281 318 14 62 6082 Aluminum Alloy T6 289 336 13 151 304 Stainless Steel Solid solution 236 516 35 157

[0122] 2. Thermal stability test

[0123] The thermal stability of the bolts was measured by keeping the bolts at 200°C for 500 hours, cooling them to room temperature, and then performing a room temperature tensile test. The results are shown in Table 2.

[0124] Table 2 Tensile test results of bolts after 500 hours of heat exposure at 200℃

[0125]

[0126]

[0127] It can be seen from Table 1 that the tensile strength and elongation of the bolts obtained in Examples 1-7 of the present invention are much higher than those of bolts made of 6061 and 6082 aluminum alloys, the yield strength thereof is higher than that of 304 stainless steel, and the tensile strength and fatigue strength thereof are also close to those of 304 stainless steel.

[0128] It can be seen from Table 2 that the thermal stability of the bolts obtained in Examples 1-7 of the present invention is much higher than that of the bolts made of 6061 and 6082 aluminum alloys, and the yield strength after heat exposure at 200°C / 500h is still higher than that of 304 stainless steel, but the tensile strength is lower than that of 304 stainless steel.

[0129] The high-strength rare earth aluminum alloy material of the present invention has obvious performance advantages over 6061 and 6082 series aluminum alloys. The high-strength rare earth aluminum alloy material of the present invention has a high processing procedure and high production efficiency. Compared with 6061 and 6082 series aluminum alloys, the production cycle is shorter and the production cost is relatively low. In addition, the present invention adds rare earth elements lanthanum (La), samarium (Sm) and ytterbium (Yb) to the aluminum alloy, which has a significant improvement effect on its performance, such as purifying the melt, refining grains, inhibiting recrystallization, improving the intermediate phase morphology, hindering dislocation migration, and improving thermal stability. The high-performance aluminum alloy material prepared by adding appropriate amounts of rare earth elements lanthanum, samarium and ytterbium is used for bolt manufacturing to meet the needs of various fields for high-performance aluminum alloy bolts.

[0130] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-strength rare earth aluminum alloy material, characterized in that: The aluminum alloy material includes the following components by weight: Si: 0.2-1.2%, Mg: 0.2-1.5%, Cu: 0.1-0.2%, Zn: 0.1-1.0%, Mn: 0.06-1.0%, Cr: 0.06-0.6%, V: 0.08-0.3%, Ag: 0.03~0.3%, Ti: 0.06~0.4%, Zr: 0.01~0.35%, Hf: 0.01~0.35%, Fe≤0.30%, La: 0.03~0.4%, Yb: 0.03~0.4%, Sm: 0.03~0.5%, other unavoidable single impurity elements ≤0.04%, the total amount of impurity elements ≤0.15%, the balance is Al.

2. The high-strength rare earth aluminum alloy material according to claim 1, characterized in that: The aluminum alloy material includes the following components in parts by weight: Si: 0.6-1.0%, Mg: 0.6-1.4%, Cu: 0.1-0.2%, Zn: 0.4-0.8%, Mn: 0.3-0.6%, Cr: 0.08-0.3%, V: 0.1-0.25%, Ag: 0.05-0.15%, Ti: 0.06-0.30%, Zr: 0.08-0.20%, Hf: 0.05-0.18%, Fe≤0.20%, La: 0.08-0.3%, Yb: 0.05-0.20%, Sm: 0.05-0.30%, other inevitable single impurity elements≤0.03%, the total amount of impurity elements≤0.15%, and the balance is Al.

3. A high-strength rare earth aluminum alloy material according to claim 1 or 2, characterized in that: The aluminum alloy material includes the following components in parts by weight: Si: 0.63%, Mg: 1.29%, Cu: 0.13%, Zn: 0.58%, Mn: 0.43%, Cr: 0.26%, V: 0.21%, Ag: 0.11%, Ti: 0.16%, Zr: 0.10%, Hf: 0.18%, Fe: 0.19%, La: 0.33%, Yb: 0.21%, Sm: 0.15%, other unavoidable single impurity elements ≤ 0.03%, the total amount of impurity elements ≤ 0.15%, and the balance is Al.

4. A method for preparing a high-strength rare earth aluminum alloy material according to any one of claims 1 to 3, characterized in that: Step (1), calculating and weighing the aluminum alloy raw material according to the mass percentage of the chemical composition of the alloy; Step (2), firstly placing the prepared Al material in a melting furnace for smelting and melting, then adding Si, Cu, Zn, Mn, Cr, and V materials for melting, and then charging Ti, Zr, Hf, Fe, La, Yb, Sm, and Ag into the smelting furnace for heating and melting, and when the smelting temperature is reached, the smelting is carried out by keeping the temperature high, and mechanically stirring the melt during the holding period to obtain melt I; Step (3), after cooling the melt I, Mg is added to the melt I for smelting, and melt II is obtained after the added charge is completely melted and fully stirred; Step (4), performing a pre-furnace component test on melt II and adjusting the chemical composition according to the test results. If the composition is qualified, argon gas is introduced into melt II for refining and slag removal to obtain melt III; if the composition is unqualified, adjusting the alloy composition according to the test results until it is qualified, and performing refining and slag removal to obtain a final qualified melt III; Step (5), discharging the melt III from the smelting furnace, and then entering a semi-continuous casting machine for casting after double-stage filtration to obtain a round rod-shaped ingot, the diameter of which is determined according to actual needs; Step (6), placing the round rod-shaped ingot into a heating furnace, heating it and keeping it warm for a certain period of time for homogenization treatment, then taking the round rod-shaped ingot out of the heating furnace and cutting it into a certain length, and the remaining round rod-shaped ingot is again placed in the heating furnace for insulation, and the cut round rod-shaped ingot is placed in an extruder to be extruded into a rod of a desired diameter, and after the extruded rod is extruded from the extruder, it enters a water tank for machine quenching to cool it to room temperature, and then the rod is straightened and cut into a desired length; Step (7), placing the extruded rod into an aging furnace for aging treatment, and after the heat preservation is completed, taking it out of the furnace and cooling it to room temperature to obtain a high-performance aluminum alloy material containing rare earth for subsequent processing.

5. The method for preparing a high-strength rare earth aluminum alloy material according to claim 4, characterized in that: In step (2), the prepared Al material is placed in a melting furnace at a melting temperature of 550 to 780°C; when the melting temperature reaches 720 to 820°C, the melting is carried out by keeping the temperature constant. In step (3), Mg is added to the melt I and the melting temperature is 680 to 780°C.

6. The method for preparing a high-strength rare earth aluminum alloy material according to claim 4, characterized in that: Features: In step (4), the temperature for refining the melt II by introducing argon gas is 700-760°C, the refining time is 30-60 minutes, and the argon gas is 99.99% high-purity argon gas.

7. The method for preparing a high-strength rare earth aluminum alloy material according to claim 4, characterized in that: Features: In step (5), the casting temperature when entering the semi-continuous casting machine for casting is 680-720°C, and the crystallizer descending speed is 80-160 mm / min.

8. The method for preparing a high-strength rare earth aluminum alloy material according to claim 4, characterized in that: Features: In step (6), the homogenization temperature is 500-575° C., the homogenization time is ≥4 hours, and the extrusion speed is 6-16 m / min. In step (7), the extruded rod is placed in an aging furnace for aging treatment at a temperature of 120-220° C. and a holding time of 3-12 hours.

9. The method for preparing a high-strength rare earth aluminum alloy material according to any one of claims 4 to 8, characterized in that: The aluminum alloy material has a yield strength of 320-350 MPa, a tensile strength of 386-410 MPa, and an elongation of 18%-27%.

10. Use of a high-strength rare earth aluminum alloy material according to any one of claims 1 to 3 in the preparation of aluminum alloy fasteners, characterized in that: The aluminum alloy fasteners include but are not limited to bolts, clamps, nuts, screws, pins or washers. The preparation method of the aluminum alloy fasteners includes the following steps: firstly, the prepared high-strength rare earth aluminum alloy material is sheared into bars of required length, then cold-forging is performed to form the required aluminum alloy fasteners, and then degreasing, pickling, alkali washing and anodizing are performed to obtain finished aluminum alloy fasteners.

Citation Information

Patent Citations

  • Aluminum alloy and preparation method thereof

    CN105714165A

  • High-strength high-toughness Al-Zn-Mg-Cu aluminum alloy and heat treatment method thereof

    CN108823472A

  • High performance Al-Mg-Si aluminum alloy extrusion material and preparation method thereof

    CN110669964A

  • High-performance rare earth Al-Mg-Si aluminum alloy extrusion material and preparation method thereof

    CN112746201A

  • Aluminum alloy for high-strength and corrosion-resistant high-pressure pump body bolt and preparation method of aluminum alloy

    CN112795821A

Cited By

  • Homogenizing heat treatment-free aluminum alloy material as well as preparation method and application thereof

    CN121046700A